Analysis of Dental Traumas and their Sequelae in the Primary Dentition: A Literature Review - Luciana Reichert da Silva Assunção; Robson Frederico Cunha; Antônio Ferelle (Association of Support to Oral Health Research (APESB), 2007)
Introduction: Studies have shown that dental traumas in the primary dentition are common events that may result in sequelae that can compromise the affected primary tooth. In the literature, the frequency of dental trauma in the primary dentition is variable, while the age range, gender, etiological factor and the most affected teeth present similar prevalence. Regarding the most common type of trauma, differences may be found due to sampling criteria, such as the type of study and site of conduction of the study. Several sequelae may be observed in traumatized primary teeth, among which coronal discoloration, pulp necrosis, root canal obliteration and root resorption. Studies have pointed to the type of trauma and the age of the child at the moment of trauma as important factors that contribute to the occurrence of these sequelae.Purpose: The purpose of this article is to present a review of relevant studies referring to epidemiological factors and sequelae in traumatized primary teeth, providing to the reader an overview of dental trauma in the primary dentition.Conclusion: In conclusion, based on the analysis of the reviewed articles, it could be observed a direct relationship between the degree of severity of the dental traumas and the occurrence of sequelae in the affected primary teeth, emphasizing the importance of periodical follow up in these cases.